Use of Chlorine Dioxide to Treat Recirculated Process Water in a Commercial Tomato Packinghouse: Microbiological and Chemical Risks - López-Gálvez, Francisco; Tudela, Juan A.; Gil, Maria I.; Allende, Ana (Frontiers in Sustainable Food Systems, 2020)
Antimicrobial treatment of fresh produce wash water can enable water reuse by avoiding microbial cross-contamination. In this study, the efficacy of chlorine dioxide (ClO2; 2–3 mg/L) to maintain the microbiological quality of process wash water in a tomato packinghouse was assessed. Different parameters were measured, including the physicochemical characteristics of the wash water [pH, oxidation-reduction potential (ORP), chemical oxygen demand (COD), absorbance at 254 nm (UVA254), temperature, electrical conductivity (EC)], the levels of different microorganisms present in water and in the product [aerobic mesophilic bacteria (AMB), total coliforms, yeasts and molds, E. coli], and the presence of chlorate as disinfection by-product. The treatment with ClO2 had a significant effect on the microbial populations present in the recirculated wash water and the tomatoes compared with the use of untreated recirculated water. The treated water showed levels of AMB, total coliforms and E. coli more than 1 logarithmic unit lower than the untreated water. The microbial load in tomatoes washed with tap water, and ClO2-treated recirculated water was similar. The transfer of chlorate from wash water to the fruits was very low under the conditions tested, with levels of chlorate in the washed product always lower than 0.05 mg/kg. The results obtained indicate that ClO2 could be a suitable option for the reuse of wash water in commercial packinghouses, as it reduces the microbial populations in wash water while not leading to the presence of disinfection by-products, such as chlorate, in the final product. This study shows that the monitorization and control of the microbiological quality of process wash water should be managed together with good practices able to guarantee hygienic conditions of the equipment by implementing efficient cleaning and disinfection systems.